Can Central Government Transfer Funds Reduce Poverty in Aceh Province? - Yunidar Purnama Sari; Nasri Bachtiar (Transpublika Publisher, 2024)
This study aims to determine the effect of central government transfer funds to regions on poverty in Aceh Province. The analytical method used in this research is the panel regression analysis method. The data used include general allocation funds, specific allocation funds, revenue-sharing funds, and poverty levels, published by the Ministry of Finance of the Republic of Indonesia and the Central Bureau of Statistics (BPS) for the districts/cities in Aceh Province from 2020 to 2023. The results of this study indicate that the General Allocation Fund (DAU) has a positive impact on poverty levels, while the Specific Allocation Fund (DAK) and Revenue Sharing Fund (DBH) have a negative impact on poverty in Aceh Province. Regional governments need to allocate the DAU not only for routine expenditures but also for productive programs focused on poverty alleviation, such as infrastructure, education, and health. Strengthening DAK and DBH programs is also essential for community empowerment in productive sectors and basic infrastructure to improve access and economic opportunities for the poor. Strict oversight of the use of DAU, DAK, and DBH is necessary to ensure funds are used in a targeted manner, avoiding projects with minimal impact. Additionally, regional self-reliance in optimizing Local Revenue (PAD) should be encouraged so that regional governments have greater flexibility in implementing poverty alleviation programs according to local needs.